Pengetahuan Lokal dalam Tradisi Ncukur Ghumbak Masyarakat Serawai Kabupaten Bengkulu Selatan - Sari, Mita Puspita; Amrizal, Amrizal; Lubis, Bustanuddin (UNIB Press, 2025)
Oral traditions are an important part of cultural heritage that contain local knowledge values and symbolic meanings passed down from generation to generation. However, the development of the times has the potential to erode public understanding of the meanings and values embedded in these traditions if they are not documented scientifically. The data obtained were analyzed using a descriptive qualitative approach through the stages of data reduction, data presentation, and conclusion drawing. The aim of this research is to describe the symbolic meaning of the device and describe local knowledge in the ncukur ghumbak tradition of the Serawai community, South Bengkulu Regency. The method used in this research is qualitative. The collection technique uses observation, interviews and documentation techniques. The results of this research show that there is a symbolic meaning to the devices used in the ncukur ghumbak tradition, namely 1) knitted flowers and money flags have the meaning of symbolizing happiness, 2) jambar has the meaning of peace 3) potpourri has the meaning of prosperity, 4) dedulang has the meaning of rice. has the meaning of hope of getting a lot of good fortune, niugh, the meaning of hope that it will be useful in the future, calico symbolizes purity, 5) the candle has the meaning of a bright future, 6) the noukur ghumbak container has the meaning of niugh mudau, has the meaning of hope that it will be useful in the future, as cool the meaning of hope to become a patient and level-headed person, njuang abang has the meaning so that children will become brave children in the future. Local knowledge in the ncukur ghumbak tradition, namely 1) throwing away the ghumbak kamah, 2) equalizing the weight of the zhumbak to the price of gold or silver following the birth of the Prophet Muhammad SAW.